1991
DOI: 10.1002/pola.1991.080290615
|View full text |Cite
|
Sign up to set email alerts
|

Ethynyl‐terminated polyethers from new end‐capping agents. II. End‐chain functionalization through nitro displacement

Abstract: Ethynyl‐terminated polysulfones and ethynyl‐terminated polyether‐ketones were prepared in a one‐step polyetherification reaction using new end‐capping agents, respectively 4‐ethynyl‐3′‐nitrodiphenylsulfone and 4‐ethynyl‐4′‐nitrobenzophenone. These reagents were prepared according to a three‐step route each. End‐capping of the polymers involve the nitro displacement by a phenoxide ion. The nitro group was found to be more reactive than the fluoro one as a leaving group. Due to the thermally induced reaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Acetylene‐ or phenylacetylene‐terminated resins can be thermally cured without giving off volatiles. Acetylene groups have been used as crosslinking reaction sites in aromatic polyimides,1, 2 poly(ether ketone sulfone)s,3, 4 polyphenylquinoxalines,5 poly(phenyl‐ as ‐triazine)s,6 Schiff base polymers,7 poly(perfluoroalkylene ether benzoxazole)s,8 poly(phenylquinozaline)s9 and polyphenylenes 10. Resins terminated with acetylene or phenylacetylene have a long shelf life and their cured products have excellent solvent resistance and favorable combination of physical and mechanical properties at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Acetylene‐ or phenylacetylene‐terminated resins can be thermally cured without giving off volatiles. Acetylene groups have been used as crosslinking reaction sites in aromatic polyimides,1, 2 poly(ether ketone sulfone)s,3, 4 polyphenylquinoxalines,5 poly(phenyl‐ as ‐triazine)s,6 Schiff base polymers,7 poly(perfluoroalkylene ether benzoxazole)s,8 poly(phenylquinozaline)s9 and polyphenylenes 10. Resins terminated with acetylene or phenylacetylene have a long shelf life and their cured products have excellent solvent resistance and favorable combination of physical and mechanical properties at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…DSC Characterization. The curing behavior of [1][2][3][4][5][6] was examined by DSC (Table 1). A DSC thermogram representative of these monomers is shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] The phenyl-ethynyl end-capped cured resins in general have shown improved thermooxidative stability and processability over thermally cured acetylene-terminated resins. [25][26][27][28][29] Our research program has built upon the NASA work and developed a variation of the phenyl-ethynyl end-capped oligomers that cure at significantly lower temperatures. 14,19,20 We found that by simply substituting the phenyl moiety with a naphthyl or anthracenyl ring a decrease in curing temperature of 30 and 80 °C, respectively, is observed.…”
Section: Introductionmentioning
confidence: 99%
“…In today's world of high energy costs and high tech applications, there continues to be a tremendous need and challenge for the development of lighter and yet mechanically more durable composite materials. One approach that has proven quite successful was initially developed by NASA involving the thermal cure of imide oligomers, which, after curing, affords a final resin with very desirable properties for use in high performance applications. Others in the field have explored variations of the phenyl−ethynyl end-capped oligomers as well as probing the mechanism of the curing process(es). The phenyl−ethynyl end-capped cured resins in general have shown improved thermooxidative stability and processability over thermally cured acetylene-terminated resins. Our research program has built upon the NASA work and developed a variation of the phenyl−ethynyl end-capped oligomers that cure at significantly lower temperatures. ,, We found that by simply substituting the phenyl moiety with a naphthyl or anthracenyl ring a decrease in curing temperature of 30 and 80 °C, respectively, is observed.…”
Section: Introductionmentioning
confidence: 99%